PENGEMBANGAN PERANGKAT PEMBELAJARAN IPA BERBASIS MODEL AUDITORY INTELLECTUALLY REPETITION UNTUK MENINGKATKAN KEMAMPUAN KOGNITIF SISWA SMP PADA MATERI TEKANAN ZAT - Alaina, Nur; Yustina, Yennita; Sahal, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The development of science learning equipment based on auditory intellectual repetition is a sequence of process to create a learning media. The set of learning equipment which was developed were the Learning Implementation Plan (RPP) and Learning Implementation Plan (RPP) and Student Worksheets (LKPD). The aim of this research was to develop a set of learning equipment which consisted by study plan and student worksheet based on auditory intellectually repetition model in pressure material. The method used in this research was research and development (R&D). The media was validated by 4 validators. The practicability of student worksheet was tested by 25 students. Descriptive analysis was used to analyze the data by calculating the mean of each indicator for validity and practice of learning equipment. The result shows the mean of lesson plan's validity is 3.91 which means in valid category. Student worksheet validity is also valid by mean 3,87. In general, the validity of learning equipment is 3.89. The student worksheet 'practicability value is 3.61 in valid category. The science learning equipment based on auditory intellectual repetition on pressure material is valid and practical and can be used in learning process in order to increase junior high school student's cognitive ability..Key Words: Learning Devices (RPP and LKPD), Auditory Intellectually Repetition, Pressure